Etiology of Acute Coronary Syndrome after Noncardiac Surgery - Helwani, Mohammad A; Amin, Amit; Lavigne, Paul; Rao, Srikar; Oesterreich, Shari; Samaha, Eslam; Brown, Jamie C; Nagele, Peter (Anesthesiology (Philadelphia), 2018)
The objective of this investigation was to determine the etiology of perioperative acute coronary syndrome with a particular emphasis on thrombosis versus demand ischemia. In this retrospective cohort study, adult patients were identified who underwent coronary angiography for acute coronary syndrome within 30 days of noncardiac surgery at a major tertiary hospital between January 2008 and July 2015. Angiograms were independently reviewed by two interventional cardiologists who were blinded to clinical data and outcomes. Acute coronary syndrome was classified as ST-elevation myocardial infarction, non-ST-elevation myocardial infarction, or unstable angina; myocardial infarctions were adjudicated as type 1 (plaque rupture), type 2 (demand ischemia), or type 4b (stent thrombosis). Among 215,077 patients screened, 146 patients were identified who developed acute coronary syndrome: 117 were classified as non-ST-elevation myocardial infarction (80.1%); 21 (14.4%) were classified as ST-elevation myocardial infarction, and 8 (5.5%) were classified as unstable angina. After coronary angiography, most events were adjudicated as demand ischemia (type 2 myocardial infarction, n = 106, 72.6%) compared to acute coronary thrombosis (type 1 myocardial infarction, n = 37, 25.3%) and stent thrombosis (type 4B, n = 3, 2.1%). Absent or only mild, nonobstructive coronary artery disease was found in 39 patients (26.7%). In 14 patients (9.6%), acute coronary syndrome was likely due to stress-induced cardiomyopathy. Aggregate 30-day and 1-yr mortality rates were 7 and 14%, respectively. The dominant mechanism of perioperative acute coronary syndrome in our cohort was demand ischemia. A subset of patients had no evidence of obstructive coronary artery disease, but findings were consistent with stress-induced cardiomyopathy.